Harboring Concerns: The Problematic Conceptual Reorientation of Juvenile Prostitution Adjudication in New York - Schwartz, Shelby (Columbia Journal of Gender and Law, 2008)
In 2003, New York City police arrested Nicolette R., a twelve-year-old girl, for offering oral sex to an undercover officer for forty dollars. Nicolette had already been arrested for prostitution in a different city, but that time her pimp paid her fine and she returned to the streets. This time was different. Prosecutors sought to sentence Nicolette to secure detention, pointing to her lack of remorse and tendency to carry weapons; her defense attorneys argued that she was a child, victimized by sexual predators, and should be set free. First a Family Court judge placed her in a secure juvenile detention center, but later an Appeals Court granted her the right to be placed in a residential treatment facility for emotionally disturbed children. Unfortunately, the only facility that accepted Nicolette had no resources to treat victims of sexual abuse or prostitution. The struggle over Nicolette’s fate is not unique; it occurs over and over in New York family courts and throughout the country. Simultaneously too young to consent to sex and in violation of criminal laws banning prostitution, juvenile prostitutes have been trapped in a contradictory system of regulations and left without any resources for their rehabilitation.